2018
DOI: 10.3389/fimmu.2018.01741
|View full text |Cite
|
Sign up to set email alerts
|

Resident Memory-Like Tumor-Infiltrating Lymphocytes (TILRM): Latest Players in the Immuno-Oncology Repertoire

Abstract: Resident memory T cells (TRM) are a recently identified subset of long-lived memory T cells that are characterized in terms of their unique surface phenotype combined with a non-recirculating pattern of localization to non-lymphoid, peripheral tissues. TRM have quickly become a key area of focus in understanding immune responses to microbial infection in so-called “barrier” tissues, and appear to be particularly critical for protection against repeat exposure at the same site. More recently, tumor-infiltrating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 74 publications
(70 reference statements)
4
25
0
Order By: Relevance
“…In fact, studies have shown that the expression of certain chemokines are positively correlated with the abundance of TILs and with postoperative survival in melanoma and colorectal cancer ( Kistner et al., 2017 ; Martinet et al., 2012 ). In addition, TILs expressing T RM marker CD103 have been shown to be enriched in tumor tissue, particularly in cancers of epithelial origin, and often correlate with improved patient survival ( Boddupalli et al., 2016 ; Djenidi et al., 2015 ; Edwards et al., 2018 ; Komdeur et al., 2017 ; Smazynski and Webb, 2018 ; Wang et al., 2016 ; Webb et al., 2015 ).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…In fact, studies have shown that the expression of certain chemokines are positively correlated with the abundance of TILs and with postoperative survival in melanoma and colorectal cancer ( Kistner et al., 2017 ; Martinet et al., 2012 ). In addition, TILs expressing T RM marker CD103 have been shown to be enriched in tumor tissue, particularly in cancers of epithelial origin, and often correlate with improved patient survival ( Boddupalli et al., 2016 ; Djenidi et al., 2015 ; Edwards et al., 2018 ; Komdeur et al., 2017 ; Smazynski and Webb, 2018 ; Wang et al., 2016 ; Webb et al., 2015 ).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…It has been shown that a subset of memory T cells does not recirculate but is maintained in peripheral tissues. Increasing evidence indicates that such T RM cells accumulate in various human cancer tissues and constitute a substantial population of TILs 10 . Indeed, in this macaque model, CD69, a marker for T RM cells, was barely expressed in circulating CD4 + and CD8 + T cells but was expressed in 56% and 64% of CD4 + and CD8 + TILs, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence indicates that a substantial population of CD8 + TILs are T RM -like cells 10 . These T RM cells have been identified by surface expression of CD103 and CD69 in both humans and mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mouse and human tumors, tumor-infiltrating CD8 T RM (referred as CD8 TIL RM ) can represent up to 30% of CD8 T cells [102,103]. The presence of tumor-infiltrating CD103 + T RM is associated with improved outcome or recurrence-free survival in many solid human cancers including melanoma, lung, ovarian, cervical, bladder, urothelial, and breast cancer [104].…”
Section: Harnessing T Rm Cells In Cancermentioning
confidence: 99%